PENINGKATAN KEMAMPUAN BERBAHASA BAKU GURU SD MUHAMMADIYAH SE-KOTA PADANGSIDIMPUAN DENGAN PENGGUNAAN MEDIA LAMAN KBBI DARING - Happy Sri Rezeki Purba; Devinna Riskiana Aritonang (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
This research was inspired of the team's observations at three Muhammadiyah elementary schools in Padangsidimpuan on the use of standard language. They found many errors these teachers made, especially in using standard words related to spelling and writing. Based on this observation, the research aimed to know the improvement of the ability of Muhammadiyah Elementary School teachers in Padangsidimpuan to use standard language assisted by the media of the KBBI Online page. This research was action research consisted of two cycles; cycles I and II. In cycle, I, there was only 19 teachers who achieved a completion score of 75 from the total of 45 teachers, and in cycle II there was an improvement to 40 people with a total percentage in cycle I of 42% and cycle II of 89% or an increase of 47%. According to the results, it can be stated that using the media KBBI online page can improve teachers’ ability to use standard language, spelling, and writing at Muhammadiyah Primary School Padangsidimpuan. Keywords: Ability; Elementary School Teachers; KBBI Online Page; Muhammadiyah Schools; Standard Language.